2020
DOI: 10.17798/bitlisfen.583338
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of Antimicrobial Activities and Hypoglycemic Effect of Sumac (Rhus coriaria L.) Syrups in Different Region

Abstract: This study aimed to determine the antimicrobial activity and hypoglycemic effect of sumac sours collected from different regions. Rhus coriaria, is the only species of rhus in Turkey. It shows spread in different regions in Turkey. Particularly, it is used as sour in Anatolia. Sumac sour is usually consumed in south provinces in Turkey. In the study, three Gram (-), three Gram (+) and 1 yeast strains obtained from the culture collection of the Microbiology Laboratory of Ordu University were used. The antimicro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Due to these components, sumac has been used as a raw material for medicines for a long time. [35] Koşar et al, [36] in their study on sumac extracts hydrolyzed with ethyl acetate and distilled water, showed that the total phenolic content was almost 100 times higher than that of water extracts. When the antimicrobial activity results of coriander extracts (Table 2) and the total phenolic substance results (Figure 3) are compared, there is a connection between phenolic components and antimicrobial activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Due to these components, sumac has been used as a raw material for medicines for a long time. [35] Koşar et al, [36] in their study on sumac extracts hydrolyzed with ethyl acetate and distilled water, showed that the total phenolic content was almost 100 times higher than that of water extracts. When the antimicrobial activity results of coriander extracts (Table 2) and the total phenolic substance results (Figure 3) are compared, there is a connection between phenolic components and antimicrobial activity.…”
Section: Discussionmentioning
confidence: 97%
“…The leaves and fruits of the sumac plant contain tannins, essential oil, organic acids, anthocyanins, fixed oils, and flavonoids. Due to these components, sumac has been used as a raw material for medicines for a long time [35] . Koşar et al., [36] in their study on sumac extracts hydrolyzed with ethyl acetate and distilled water, showed that the total phenolic content was almost 100 times higher than that of water extracts.…”
Section: Discussionmentioning
confidence: 99%